SISTEM MONITORING SUHU PADA RUANG OVEN KERTAS MENGGUNAKAN PID - Brika Bayu Pringgo Utomo; Aripin Triyanto (CV. Multi Kreasi Media, 2024)
Production of paper or paper core requires a drying oven which functions to reduce the moisture level of the paper. With a paper drying oven capacity of 1 ton, it causes temperature values in the room, which can affect production results. The resulting product has a moisture level that is too low <8%, so it is not straight. One of the influencing factors is environmental temperature and several other factors. So we need a system that regulates temperature stably and accurately. The proportional integral derivative control system or PID is a general control method in the context of process control which is used to maintain the value of a process variable at the desired set point (Closed Loop System). The advantages of PID systems include the ability to adapt to changing conditions quickly and effectively. However, optimal results require careful parameter tuning and adjustment according to the specific characteristics of the controlled system. The research method involves installing an electrical panel, using software in the form of thermo controls, thermocouples. During the research process, adjust the values of the PID parameters to the ideal temperature. The tuning process is carried out to obtain optimal PID parameters, achieving a fast and stable response to load variations. The research results show the application of PID with proportional parameters, so that data is obtained for 5.5 seconds. Meanwhile, in the integral, data was obtained for 108 seconds. Data reduction of 22 seconds optimized with a temperature point of 600C, with a time of 2 days. The aim of this research is to achieve the desired set point so that the resulting response is good in maintaining temperature stability and PID system performance. Production of paper or paper core requires a drying oven which functions to reduce the moisture level of the paper. With a paper drying oven capacity of 1 ton, it causes temperature values in the room, which can affect production results. The resulting product has a moisture level that is too low <8%, so it is not straight. One of the influencing factors is environmental temperature and several other factors. So we need a system that regulates temperature stably and accurately. The proportional integral derivative control system or PID is a general control method in the context of process control which is used to maintain the value of a process variable at the desired set point (Closed Loop System).